2017
DOI: 10.1111/jav.01071
|View full text |Cite
|
Sign up to set email alerts
|

Migration strategies and annual space‐use in an Afro‐Palaearctic aerial insectivore – the European nightjar Caprimulgus europaeus

Abstract: Obligate insectivorous birds breeding in high latitudes travel thousands of kilometres during annual movements to track the local seasonal peaks of food abundance in a continuously fluctuating resource landscape. Avian migrants use an array of strategies when conducting these movements depending on e.g. morphology, life history traits and environmental factors encountered en route. Here we used geolocators to derive data on the annual space‐use, temporal pattern and migratory strategies in an Afro‐Palaearctic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 60 publications
5
51
0
Order By: Relevance
“…Although the tracked nightjars bred in a relatively restricted area in Denmark (within 65 km), they dispersed over a much larger area in Africa and spent the winter outside the former known winter areas in Africa which do not include the central parts of the continent [20,31] although three European nightjars from England and several from Sweden spent the winter in the same area as the birds from Denmark [32,33]. Our tracks of swifts were similar to those already published from other North European populations [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the tracked nightjars bred in a relatively restricted area in Denmark (within 65 km), they dispersed over a much larger area in Africa and spent the winter outside the former known winter areas in Africa which do not include the central parts of the continent [20,31] although three European nightjars from England and several from Sweden spent the winter in the same area as the birds from Denmark [32,33]. Our tracks of swifts were similar to those already published from other North European populations [22].…”
Section: Discussionmentioning
confidence: 99%
“…In most avian species studied so far, spring migration occurs faster than fall migration, possibly because of constraints in the arrival time at the breeding area [36]. Norevik et al [33] reported faster fall than spring migration in European nightjars. We found a similar, but non-significant difference, which contrasted the pattern in swifts and cuckoos, where spring migration is faster than fall migration [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the inconsistent patterns of advancements in the timing of migration reported in some but not all cases [79][80][81] . At least in some species, it is well possible that the scheduling of migration depends more strongly on the animal's endogenous rhythms and photoperiodism 82,83 than on temperature cues. If birds solely rely on photoperiodic cues and/or endogenous rhythms to initiate their migration, they may be too inflexible to accommodate phenology changes, for example during their subsequent arrival at the breeding grounds, unless they adjust the speed of migration to conditions en route 84,85 or shorten their migration distances 75 .…”
Section: Adjusting the Time Program To Keep Pace With Global Changementioning
confidence: 99%
“…In the same line of thinking, relatively high fuelling rates will limit the time and energy spent at stopovers resulting in similar benefits of detoured routes in front of barriers where large fuel loads are required (Lindström et al, ). We note that some northbound nightjars stop for several weeks just before reaching the Sahara in spring, presumably to fuel for the subsequent barrier crossing (Evens et al, ; Jacobsen et al, ; Norevik et al, ). Like nightjars within the Palaearctic–African migration system, common swifts Apus apus undertake large detours via West Africa that, combined with favourable winds for north migration, coincide well with the spring rains in Liberia and the associated massive emergence of aerial insect prey (Åkesson et al, , ).…”
Section: Discussionmentioning
confidence: 80%
“…Individual positioning data are provided in the original tracking studies (Evens et al, 2017;Jacobsen et al, 2017;Norevik et al, 2017). Location data and raw data for the simulations are available at the Dryad Digital Respository https ://doi.org/10.5061/dryad.ms1fm8p (Norevik et al, 2019).…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%